The essential roles of lncRNAs/PI3K/AKT axis in gastrointestinal tumors - Li, Penghui; Ma, Xiao; Gu, Xinyu (Frontiers in Cell and Developmental Biology, 2024)
The role of long noncoding RNA (lncRNA) in tumors, particularly in gastrointestinal tumors, has gained significant attention. Accumulating evidence underscores the interaction between various lncRNAs and diverse molecular pathways involved in cancer progression. One such pivotal pathway is the PI3K/AKT pathway, which serves as a crucial intracellular mechanism maintaining the balance among various cellular physiological processes for normal cell growth and survival. Frequent dysregulation of the PI3K/AKT pathway in cancer, along with aberrant activation, plays a critical role in driving tumorigenesis. LncRNAs modulate the PI3K/AKT signaling pathway through diverse mechanisms, primarily by acting as competing endogenous RNA to regulate miRNA expression and associated genes. This interaction significantly influences fundamental biological behaviors such as cell proliferation, metastasis, and drug resistance. Abnormal expression of numerous lncRNAs in gastrointestinal tumors often correlates with clinical outcomes and pathological features in patients with cancer.Additionally, these lncRNAs influence the sensitivity of tumor cells to chemotherapy in multiple types of gastrointestinal tumors through the abnormal activation of the PI3K/AKT pathway. These findings provide valuable insights into the mechanisms underlying gastrointestinal tumors and potential therapeutic targets. However, gastrointestinal tumors remain a significant global health concern, with increasing incidence and mortality rates of gastrointestinal tumors over recent decades. This review provides a comprehensive summary of the latest research on the interactions of lncRNA and the PI3K/AKT pathway in gastrointestinal tumor development.Additionally, it focuses on the functions of lncRNAs and the PI3K/AKT pathway in carcinogenesis, exploring expression profiles, clinicopathological characteristics, interaction mechanisms with the PI3K/AKT pathway, and potential clinical applications.